Computing with electromagnetic fields rather than binary digits: a route towards artificial general intelligence and conscious AI - McFadden, Johnjoe (Frontiers in Systems Neuroscience, 2025)
McFadden’s conscious electromagnetic information (CEMI) field theory proposes that the human brain functions as a hybrid digital-EM field computer. The digital computations are implemented by the matter-based neuronal-synaptic network analogous to conventional digital computers operating Boolean-like logic gates nonconsciously and in parallel. Yet neuronal electrical firing and synaptic transmission generate the brain’s immaterial but equally physical endogenous electromagnetic (EM) input into the brain’s CEMI field. The CEMI field is proposed to implement analogue information processing through constructive and destructive wave mechanical interference. The output of this field-based processing is uploaded by EM field-sensitive neurons via voltage-gated ion channels to generate conscious actions. According to the theory, non-conscious brain processing occurs solely within the EM field-insensitive digital neuronal network, enabling fast, parallel computations, but cannot form complex, integrated concepts, so it is limited to specialised functions necessary for tasks like motor coordination. In contrast, conscious thought arises from EM field interactions, where integrated information is encoded and processed holistically to deliver general intelligence and creativity as its output. Because the brain’s EM field is singular, conscious processing occurs serially, allowing our mind to hold only one thought at a time. This paper proposes a route towards developing novel hybrid computers that, like the human brain, similarly operate both modes of computation to deliver general intelligent and potentially conscious AI.